A missense mutation in NR5A1 causing female to male sex reversal: A case report. (9th April 2020) - Askari, Masomeh; Rastari, Mandana; Seresht‐Ahmadi, Mehrshad; McElreavey, Kenneth; Bashamboo, Anu; Razzaghy‐Azar, Maryam; Totonchi, Mehdi
Abstract: Testicular disorder of sex development (TDSD) is a rare condition, characterised by a female karyotype, male phenotype, small testes and cryptorchidism. Only a few studies have investigated the genetic causes of male sex reversal. This is the clinical report of an Iranian 46, XX patient presented with TDSD and associated with hypospadias. Whole‐exome sequencing (WES) of the patient ascertained the heterozygous missense variant (c.274C>T) in the NR5A1 gene, resulting in a substitution of arginine with tryptophan. The arginine 92 residue was located in a highly conserved region of steroidogenic factor 1 (SF1), which is crucial for its interaction with DNA. Our finding is in line with previous reports, which highlighted the role of p.(Arg92Trp) variant in TDSD individuals. As far as we are aware, this is the first report of TDSD with p.(Arg92Trp) variant in the Iranian population.